2019
DOI: 10.1038/s41893-019-0223-4
|View full text |Cite
|
Sign up to set email alerts
|

An analytical framework for spatially targeted management of natural capital

Abstract: Wood, Claire M.; Schmucki, Reto; Bullock, James M.; Eigenbrod, Felix. 2019. An analytical framework for spatially targeted management of natural capital. Nature Sustainability, 2 (2). 90-97.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 73 publications
(94 reference statements)
0
48
0
Order By: Relevance
“…It can only be concluded that impacts are highly heterogeneous and context-specific, with positive, negative, or neutral management effects on a range of biodiversity metrics. We therefore caution against the promotion by governments of the biodiversity value in traditional forest-management practices, such as through the Satoyama Initiative, until an understanding of the effects of scale-dependent management interventions is achieved (Spake et al, 2019). We note, however, that management can provide other benefits including the enhancement of cultural ecosystem services.…”
Section: Effect Of Traditional Secondary Forest Management On Biodimentioning
confidence: 93%
See 2 more Smart Citations
“…It can only be concluded that impacts are highly heterogeneous and context-specific, with positive, negative, or neutral management effects on a range of biodiversity metrics. We therefore caution against the promotion by governments of the biodiversity value in traditional forest-management practices, such as through the Satoyama Initiative, until an understanding of the effects of scale-dependent management interventions is achieved (Spake et al, 2019). We note, however, that management can provide other benefits including the enhancement of cultural ecosystem services.…”
Section: Effect Of Traditional Secondary Forest Management On Biodimentioning
confidence: 93%
“…Japan presents an ideal opportunity to test for such 'cross-scale interactions' (Peters, Bestelmeyer, & Turner, 2007), because of its wide climatic and topographic gradients that could potentially modify biodiversity responses to the management of its vast forest estate (Spake et al, 2019;Yamaura, Amano, Kusumoto, Nagata, & Okabe, 2011). Future studies of all forests should measure community attributes other than species richness that capture ecosystem function, in addition to reporting attributes of scale and the topographic and regional climatic context, to permit testing for interacting effects.…”
Section: Ensuring the Maintenance Of Forest Biodiversity Within Japmentioning
confidence: 99%
See 1 more Smart Citation
“…Generalised linear models were fitted to quantify how richness and abundance and the community-level trait mean and trait diversity values varied with environmental drivers including temperature and landscape heterogeneity variables, and their interactions (Spake et al 2019a). Models of total abundance and richness values (both comprising count data) were fitted via a generalised linear model with a negative binomial distribution and log link function, while normal error distributions and an identity link function were used for individual trait mean and trait diversity values.…”
Section: Statistical Modelling Of Taxonomic and Functional Diversity mentioning
confidence: 99%
“…We applied a recently developed framework (Spake et al 2019a), to test for and quantify cross-scale interactions that drive variability in forest bird community responses (trait composition and diversity) to landscape heterogeneity using a national-scale standardized monitoring dataset. This framework helps to reveal how different regional contexts might constrain or modify the effects of local drivers on a phenomenon in question, allowing an understanding of contextdependence.…”
Section: Introductionmentioning
confidence: 99%